(untitled) (Raparin Journal of Humanities (RJH), 2025)
The main aim of this study is to determine the level each of (exposure to social media and media literacy and to determine the difference in the level each of exposure to social media and media literacy according to variables (Specialist in Education and university. The researcher used descriptive-survey method and the research community includes students of four universities (Salah al-Din, Duhok, Sulaimani and Halabja) for the academic year (2024-2025) which numbers (70241) students، the sample research consist of (385) student’s those are elected bye (Proportional Stratified Sampling) from each university. To measure the level of exposure to social media and media literacy, the researcher prepared a scale in collaboration with the supervisor that consists of (8) questions and (24) items and doing psychometric face validity is (%90) and reliability is (.89). For analyze data the researcher used (SPSS.V.27) and used many static articles such (One sample T-test, Independent sample t-test, One way-ANOVA, Pearson correlation, Guttmann and cronbach’s Alpha ) the results showed that the study sample had low exposure to social media and high level of media literacy, and there is a statistically significance difference in the level social media exposure according to educational specialty and university, in the other hand there is’t statically significance the level of media literacy according to educational specialty but there is statically significance according to university, the sulaimani university student’s had higher level media literacy compare than othr universities students. Finally, the researcher made a number of recommendations in the light of the results.